IMPLIKASI PRINSIP CAVEAT VENDITOR TERHADAP PERKEMBANGAN HUKUM PERLINDUNGAN KONSUMEN DI INDONESIA - Deviana Yuanitasari (Arena Hukum, 2017)
Abstract The former emphasizes on the consumer’s awareness of his own protection, whereas the latter has its emphasis on the initiative of the producers to protect their consumers. Based on the shift, the producers have to be cautious before releasing goods and services to the market.However, in practice there are still many producers who disregard this principle.A good instance of example would be the consumer protection cases concerning hidden defects. Such cases should not happen if the principle of caveat venditor is properly implemented. The purpose of this research is to know the implication of thecaveat venditorprinciple for goods and services, and its development in consumer protection law in Indonesia and  to know the legal system of Indonesia adopt the caveatvenditor principle in order to protect Indonesian consumers.The research method utilizes normative juridical approach to assess and examine the legal and economic aspects in the national economy, in particular,the implication of the implementation of caveat venditorprinciple. Untuk itu  ditentukan spesifikasi penelitian yang digunakan adalah deskriptif-analitis. For that purpose, the specification of the research is descriptive-analytical. Adapun data yang diperoleh berasal dari data kepustakaan sebagai sumber data sekunder, serta untuk menunjang dan melengkapinya dilakukan wawancara untuk mendapatkan data primer, dan dari data yang terkumpul dianalisis secara kualitatif yuridis.The data obtained from study of literature is utilized as secondary data. Interviews were conducted to obtain primary data. The data were analyzedby juridical qualitative method.  The results of the study shows, first: the implementation of caveat venditor principle in Indonesia has not been properly conducted because of the common perception that consumers’ opinion are less valuable than producers’. The unequal treatment is used by producers to act as they please, often ignoring the existing principles. Second: The adoption of the caveat venditor principle for consumer protection by Indonesian Legal policy is shown by Law Number 8 Year 1999 about Consumer Protection (UUPK), whichis based on the principle of fault liability, utilizing reversed burden of proof. This way, both parties are protected, because it proportionally distributes the liability to each party; i.e. consumers only prove the losses they suffered, whereas producers are burdened to prove that there has been no negligence on their part.  AbstrakSuatu prinsip hubungan yang semula menekankan pada kesadaran konsumen untuk melindungi dirinya sendiri berubah menjadi kesadaran pelaku usaha untuk melindungi konsumen. Berdasarkan prinsip ini setiap pelaku usaha sebelum memasarkan poduknya sudah seharusnya berhati-hati, pada kenyataannya dalam praktik masih banyak pelaku usaha yang tidak memperdulikan prinsip ini. Tujuan dari penulisan artikel ini adalah untuk mengetahui implikasi yuridis prinsip caveat venditor yang dilaksanakan oleh pelaku usaha baik dalam bidang konsumen barang maupun jasa dan untuk mengetahui kebijakan hukum Indonesia dalam mengadopsi prinsip caveat venditor dengan tujuan untuk melindungi konsumen dalam rangka hukum perlindungan konsumen di Indonesia. Penelitian ini merupakan Penelitian Hukum Normatif. Hasil penelitian menunjukkan bahwa prinsip caveat venditor yang dilaksanakan oleh pelaku usaha belum sepenuhnya berjalan dengan baik, karena pendapat konsumen itu lebih rendah dari pelaku usaha masih digunakan oleh pelaku usaha di Indonesia, Kedua kebijakan hukum Indonesia dalam mengadopsi prinsip caveat adalah bahwa UUPK menganut prinsip tanggung gugat berdasarkan kesalahan dengan beban pembuktian terbalik.